PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Yuliyanti, Leni (JURNAL PENDIDIKAN AKUNTANSI & KEUANGAN, 2014)
The objective  of  this  research was to discover  the  effects  of  Good Corporate Governance(CGC)  and  Corporate  Social  Responsibility  (CSR)  disclosure  on  firm  value.  This  studyemployed a descriptive-verifying method. The population in this study was the companies listedin  the  IICGP ranking,  selected  through  purposive  sampling  technique.  The  data  collectiontechnique  utilized  documentation  study  with  descriptive  analysis  technique  and  classicalassumption tests;  F test  and t  test.  The results  of  the study demonstrated that  GCG gavesignificant positive effect on firm value, CSR disclosure gave significant positive effect on firmvalue, as well as GCG and CSR disclosure gave significant positive effect on firm value.